Fishery - Muhammad Abu Bakar Siddik; Md Abu Hanif; Md Reaz Chaklader; Ashfaqun Nahar; Sultan Mahmud (Egyptian Journal of Aquatic Research, 2015)
The aim of the present study was to establish the baseline data on fishery biology of Sillaginopsis panijus which is very endemic in the southern coastal waters of Bangladesh. Altogether 300 individuals of S. panijus were sampled from five catchment areas within the Ganges delta in which males represent 46% and females 54% of the total sampled population. The overall sex ratio in the populations agrees with the expected value of 1:1 in normal population. The values of allometric coefficient (b) of the LWRs indicated positive allometric growth (b > 3) in female and combined sexes, while male showed a negative allometric growth (b < 3). All the relationships among length parameters (SL–TL, SL–FL and TL–FL) of the species were found significant with all (r2) values being >0.900. The mean values of CFs for males were higher than those of females in all different length classes. The study would expedite future studies on population assessment and sustainable conservation of the fish species along the southern coastal region of Bangladesh.